Hubungan Antara Kecerdasan Matematis-Logis Dengan Hasil Belajar Ilmu Pengetaahuan Alam Siswa Kelas VI SDN Sawotratap I Gedangan - Amat Santoso (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
This study is a correlational study, which aims to determine the relationship between logical-mathematical intelligences with science learning outcomes in the sixth grade students of SDN Sawotratap I Gedangan. The population in this study is SDN Sawotratap I Gedangan. The samples come from the entire sixth grade students totaling 169 students.The data was collected by using a mathematical-logical intelligence tests and documentation of the Natural Sciences learning outcomes. Logical-mathematical intelligence test consists of 15 items derived from internet inquiries. While the documentation of the Natural Sciences learning outcomes derived from the average value of 4 times daily tests. Daily tests developed and implemented by the teacher concerned.The results of this study indicate there is a relationship between mathematical-logical intelligence with science learning outcomes. Logical-mathematical intelligence correlation with learning outcomes IPA (rxy) of 0,510 with moderate category.